Soil Fungal:Bacterial Ratios Are Linked to Altered Carbon Cycling - Malik, Ashish A.; Chowdhury, Somak; Schlager, Veronika; Oliver, Anna; Puissant, Jeremy; Vazquez, Perla G. M.; Jehmlich, Nico; von Bergen, Martin; Griffiths, Robert I.; Gleixner, Gerd (Frontiers in Microbiology, 2016)
Despite several lines of observational evidence, there is a lack of consensus on whether higher fungal:bacterial (F:B) ratios directly cause higher soil carbon (C) storage. We employed RNA sequencing, protein profiling and isotope tracer techniques to evaluate whether differing F:B ratios are associated with differences in C storage. A mesocosm 13C labeled foliar litter decomposition experiment was performed in two soils that were similar in their physico-chemical properties but differed in microbial community structure, specifically their F:B ratio (determined by PLFA analyses, RNA sequencing and protein profiling; all three corroborating each other). Following litter addition, we observed a consistent increase in abundance of fungal phyla; and greater increases in the fungal dominated soil; implicating the role of fungi in litter decomposition. Litter derived 13C in respired CO2 was consistently lower, and residual 13C in bulk SOM was higher in high F:B soil demonstrating greater C storage potential in the fungal:bacterial dominated soil. We conclude that in this soil system, the increased abundance of fungi in both soils and the altered C cycling patterns in the fungal:bacterial dominated soils highlight the significant role of fungi in litter decomposition and indicate that F:B ratios are linked to higher C storage potential.